19F MRI-fluorescence imaging dual-modal cell tracking with partially fluorinated nanoemulsions - Tang, Ting; Zhu, Qiang; Liu, Shuang; Dai, Hailong; Li, Yu; Tang, Caihong; Chen, Kexin; Jiang, Mou; Zhu, Lijun; Zhou, Xin; Chen, ShiZhen; Zheng, Zitong; et al. (Frontiers in Bioengineering and Biotechnology, 2022)
As a noninvasive "hot-spot" imaging technology, fluorine-19 magnetic resonance imaging (19F MRI) has been extensively used in cell tracking. However, the peculiar physicochemical properties of perfluorocarbons (PFCs), the most used 19F MRI agents, sometimes suffer low sensitivity, poor cell uptake, and misleading results. In this study, a partially fluorinated agent, perfluoro-tert-butyl benzyl ether, was employed to formulate 19F MRI-fluorescence imaging (FLI) dual-modal nanoemulsion for cell tracking. Compared with PFCs, the partially fluorinated agent showed considerably improved physicochemical properties, such as lower density, shorter relaxation times, and higher solubility to fluorophores, while maintaining the high 19F MRI sensitivity. After being formulated into stable, monodisperse, and paramagnetic Fe3+-promoted nanoemulsions, the partially fluorinated agent was employed in 19F MR-FL dual imaging tracking of lung cancer A549 cells and macrophages in an inflammation mouse model.